Role of Diffusion Tensor Imaging in Grading of Brain Tumors and Assessment of White Matter Tract Invasion - Singh, Resham; Mehra, Shibani; Charan, Bheru Dan (Asian Journal of Neurosurgery, 2025)
Diffusion tensor imaging (DTI) is a novel advancement of nuclear magnetic resonance that provides an accurate, noninvasive evaluation of brain tumors and their orientation to the adjacent white matter tract. We sought to analyze DTI's role in grading brain tumors and determining white matter tract involvement.DTI with the “ep2d_diff_mddw_20_(DTI)” sequence was done in 48 individuals with brain tumors (22 low-grade and 26 high-grade). The DTI measurements, including fractional anisotropy (FA) and apparent diffusion coefficient (ADC), were checked in the tumor itself, the tumor margin, and the area around the tumor. After comparing the results between the two groups, the cutoff was determined using the receiver operating characteristic curve. Tensor maps were obtained by tractography to observe white matter tract involvement.Mean FA values in the intratumoral region and tumor margins were substantially lower in high-grade than low-grade tumors (p-value < 0.05). FA values greater than 0.12 intratumorally (sensitivity = 69.23% and specificity = 63.64%) and 0.26 at the tumor margin (sensitivity = 65.38% and specificity = 68.18%) can distinguish low-grade from high-grade brain tumors. The two groups' FA values for peritumoral edema and ADC values in different places did not significantly differ. Displacement of tracts was significantly associated with low-grade tumors, while high-grade tumors showed significantly more degrees of disruption, tract infiltration, and tract edema (p-value < 0.001).DTI is a modern and effective method for predicting tumor aggressiveness and tract involvement in the tumor's surroundings before surgery.
Keywords: brain; glioma; invasion; tract; tumor